HAS THE PLATE BOUNDARY SHIFTED FROM CENTRAL HOKKAIDO TO THE EASTERN PART OF THE SEA OF JAPAN? - Kato N.; Sato H.; Orito M.; Hirakawa K.; Ikeda Y.; Ito T. (My University, 2004)
A NS trending Cenozoic fold-and-thrust belt has developed in the western part of the Hidaka Collision Zone (HCZ), central Hokkaido, Japan. A quantitative estimation of the late Cenozoic convergence rate at the front of the Hidaka thrust system is important in revealing the plate tectonic framework around northern Japan. High-resolution seismic reflection profiling across the active fault-related folds was carried out to ascertain the temporal change in the crustal shortening rate. Overlapping ramp anticlines and growth folds within thrust sheets were examined using balanced cross-sections combined with industry seismic and drilling data. The rate of shortening was examined using a 3.5 Ma horizon and late Quaternary horizons at 115 and 41 ka. These horizons show that the convergence rate of the Hidaka thrust system has not decreased during the last 3.5 Ma. This suggests that the plate boundary between the Eurasian (Amurian) and North American (Okhotsk) plates has not jumped from the central part of Hokkaido to the eastern part of the Sea of Japan since 3.5 Ma and that a significant amount of plate convergence is still being absorbed in the Hidaka Collision Zone.
Keywords: Growth-fault-related fold; Active folding; High-resolution seismic reflection profiling; Collision zone; Plate boundary; Hidaka thrust system; Hokkaido